2013
DOI: 10.7314/apjcp.2013.14.11.6821
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue Sarcomas in the Asia-Pacific Region: A Systematic Review

Abstract: Asian Pac J Cancer Prev, 14 (11), [6821][6822][6823][6824][6825][6826][6827][6828][6829][6830][6831][6832] Introduction Soft-tissue sarcomas (STS) are a heterogeneous group of rare tumours. More than 50 STS histotypes have been identified, with most having unique clinical, prognostic, and therapeutic features. Although less than 1% of all adult malignant tumours are STS (Fletcher et al., 2002a), their treatment and management is complex because many tumour-related (eg, histotype, site, size, depth, grade, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…However, the median tumor size of 9 cm in both the chemotherapy and non-chemotherapy groups in this study were larger than the median tumor size of 8.6 cm and 7.5 cm in the chemotherapy and non-chemotherapy groups in the EORTC trial, respectively 12 . The predominant histological subtype in this study was UPS (26/58, 45%), which is higher than the 29% and 18% rates reported from the ISG trial 9 , EORTC trial 13 , respectively, but similar to 27% rate reported by Roger et al 19 Synovial sarcoma in this study was 8.9% (5/58), which is considerably lower than the 25% rate in the ISG and the 14% rate in the EORTC trial 9,13 . A total of 87% (50/58) of patients had negative surgical margin, which was higher than 37%, 38% and 37% reported in the EORTC, Taiwan and Korean studies, respectively 13,18,20 .…”
Section: Discussionsupporting
confidence: 60%
“…However, the median tumor size of 9 cm in both the chemotherapy and non-chemotherapy groups in this study were larger than the median tumor size of 8.6 cm and 7.5 cm in the chemotherapy and non-chemotherapy groups in the EORTC trial, respectively 12 . The predominant histological subtype in this study was UPS (26/58, 45%), which is higher than the 29% and 18% rates reported from the ISG trial 9 , EORTC trial 13 , respectively, but similar to 27% rate reported by Roger et al 19 Synovial sarcoma in this study was 8.9% (5/58), which is considerably lower than the 25% rate in the ISG and the 14% rate in the EORTC trial 9,13 . A total of 87% (50/58) of patients had negative surgical margin, which was higher than 37%, 38% and 37% reported in the EORTC, Taiwan and Korean studies, respectively 13,18,20 .…”
Section: Discussionsupporting
confidence: 60%
“…Some retrospective analysis shows nearly all patients are treated with surgery, and more studies use adjuvant radiotherapy than chemotherapy (Ngan et al, 2013;Yetisyigit et al, 2013). In an effort to complement surgery, with inherent limitations of resection and high recurrence and the canceration rate of LPS, the administration of other treatment modalities, such as radiation therapy and chemotherapy, has been tried (Cui et al, 2012;Gronchi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…3 – 9 In recent years, an increasing incidence of STS has also been revealed in several studies. 3 – 6 However, specific data on STS in the Asia-Pacific region are rare, 10 and only 2 studies reporting the incidence patterns of sarcomas in Asia are available. 11 , 12 By using the nationwide Taiwan Cancer Registry (TCR) database, the incidences related to bone cancer in the Taiwanese population have been reported in our previously published results.…”
Section: Introductionmentioning
confidence: 99%